The effect of Dopamine Agonists on patients with advanced Parkinson's disease subjected to subthalamic deep brain stimulation. (c2000) - Jabre, Mazen Gerges (2000)
Parkinson's disease (PO) is a neurodegerative disorder predominantly characterized by the progressive loss of dopaminergic cells in the substantia nigra pars compacta (SNPC). Striatal dopamine concentration gets significantly reduced, and clinical symptoms, especially the motor handicap, prevail. The management of this disease is symptomatic, mainly based on the use of levodopa. Due to the high incidence of adverse effects associated with its chronic use, alternative treatments based on the direct-acting dopamine agonists have been used. Deep brain stimulation has been proposed as an alternative effective treatment for advanced PO cases disabled by the high incidence of levodopa-induced motor complications. High frequency stimulation of the subthalamic nucleus (STN HFS) alleviated the severe motor disabilities associated with PO; however, a postoperative , pharmacological strategy has not been established yet. The following study reports and investigates the efficacy, safety and tolerability of a postoperative therapeutic approach mainly based on dopamine agonists. We run a pilot, prospective, and open-label study on five patients with severe idiopathic PO who underwent STN HFS. Their postoperative management mainly consisted of dopamine agonist, while levodopa was considered as a rescue therapy. Efficacy, safety and tolerability outcome measures were determined 12 weeks after surgery using the Unified Parkinson's Disease Rating Scale motor part (UPDRS-III), UPDRS part IV (complications of therapy) and the Hoehn and Yahr staging scale. Three months after surgery, all patients were effectively maintained on dopamine agonist-based therapy with an 88% improvement in UPDRS motor subscore (p <0.01). Dyskinesias, motor fluctuations, and levodopa-equivalent daily dose requirements decreased by 82.35%,82.14%, and 77%, respectively (p<O.OI). The mean levodopa dose was reduced by 90% (p < 0.01), while the mean dopamine agonist dose was increased by 15% from preoperative level. Reported adverse events were mild and transient. Our preliminary study suggests that STN HFS is a safe and effective approach in the treatment of advanced PD. Postoperative dopamine agonist monotherapy can potentially be proposed in controlling residual motor disability before adding levodopa.